Identifying the Comprehensive Consumer’s Post-Covid Behavioral Pattern in Meta Platform - Mahsa Akbari; Mostafa Bigdeli; Abbas khamseh (International Journal of Web Research)
Given a limited understanding of post-COVID customer behavior on social media, this paper seeks to identify consumer behavioral patterns on Facebook and Instagram in the post-COVID era. The research explores all the inner and outer features that might affect the way consumers think or act in the post-COVID era. Hence, a qualitative approach has been adopted to have a more comprehensive and current understanding. The research begins by identifying pertinent factors shaping consumer behavior through an extensive review of existing literature. To refine and validate these factors, the study employs the fuzzy Delphi method, a research technique that involves seeking consensus among a panel of experts. The findings of the research illuminate 24 distinct factors, organized into five main dimensions: contextual, social, content, technological, and product. Notably, the study underscores the significance of product-related factors, technological advancements, content quality, and social interactions in shaping post-COVID consumer behaviors. The product-related factors hold the most substantial influence over consumer behaviors, followed by technological considerations, content quality, and social interactions. Managers should prioritize quality assurance and strategic product categorization. Emphasizing these aspects in product positioning can significantly influence consumer behavior on social media platforms.